f *) (3 – 2^4).7^3=2.7^4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 219-7x-7=100
212-7x=100
7x=112
x=16
các câu còn lại cứ thế mà làm
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow3x-16=2.7^4+7^3=5145\Leftrightarrow3x=5161\Leftrightarrow x=\dfrac{5161}{3}\)
\(\left(3x-2^4\right)-7^3=2.7^4\\ \Leftrightarrow\left(3x-16\right)=2.7^4+7^3\\ \Leftrightarrow3x-16=5145\\ \Leftrightarrow3x=5145+16=5161\\ \Leftrightarrow x=\dfrac{5161}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\((3.x-2^{4} ):7^3 =2.7^{4}\)
\(=>(3.x-16):7^{3} =2.7^{4}\)
\(=>3.x-16=2.7^{4}:7^{3}\)
\(=>3.x-16=2.7^{4-3}\)
\(=>3.x-16=2.7\)
\(=>3.x-16=14\)
\(=>3.x=14+16\)
\(=>3.x=30\)
\(=>x=30:3\)
\(=>x=10\)
\(\left(3x-2^4\right):7^3=\left(2.7\right)^4\)
\(\Rightarrow\left(3x-2^4\right)=2^4.7^4.7^3\)
\(\Rightarrow3x-2^4=2^4.7^7\)
\(\Rightarrow3x=2^4.7^7+2^4\)
\(\Rightarrow3x=2^4.\left(7^7+1\right)=16\left(7^7+1\right)\)
\(\Rightarrow x=\dfrac{16\left(7^7+1\right)}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3x-2^4\right).7^3=2.7^4\\ \Leftrightarrow3x-16=2.7^4:7^3\\ \Leftrightarrow3x=14+16\\ \Leftrightarrow3x=30\\ \Leftrightarrow x=10\)
Vậy...
\(\left(2x-2^4\right).7^3=2.7^4\)
\(\Leftrightarrow\left(2x-2^4\right)=2.7^4:7^3\)
\(\Leftrightarrow2x-2^4=2.7\)
\(\Leftrightarrow2x-16=14\)
\(\Leftrightarrow2x=30\)
\(\Leftrightarrow x=15\)
Vậy ..
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3x-2^4\right).7^3=2.7^4\)
\(\left(3x-2^4\right)=2.7^4\div7^3\)
\(3x-2^4=2.7\)
\(3x-2^4=14\)
\(3x=14+2^4\)
\(3x=30\)
`=>` \(x=30\div3\)
`=> x=10`
![](https://rs.olm.vn/images/avt/0.png?1311)
(3.x - 2^4) . 7^3 = 2. 7^4
(3.x - 16) . 343 = 2 . 2401
(3.x - 16) . 343 = 4802
3.x - 16 = 4802 : 343
3.x - 16 = 14
3.x = 14 + 16
3.x = 30
x = 30 : 3
x = 10
![](https://rs.olm.vn/images/avt/0.png?1311)
/x-3/=7-(-2)
/x-3/=9
x=/9+3/
x=/12/
x=/12/
<=> x= 12; -12
( 3x-24)*73=2*74
(3x-16)*343=4802
3x-16=14
3x=14+16
3x=30
=> x = 10
x-[42+(-28)]=-8
x-14=8
x=8+14
x=22
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3x-2^4\right).7^3=2.7^4\Leftrightarrow3x-2^4=\dfrac{2.7^4}{7^3}=2.7=14\)
\(\Leftrightarrow3x-16=14\Leftrightarrow3x=14+16=30\Leftrightarrow x=\dfrac{30}{3}=10\) vậy \(x=10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(3.x-24).73=2.74
(3.x-16).343=2.2401
(3.x-16).343=4802
3.x-16=4802:343
3.x-16=14
3.x=14+16
3.x=30
x=30:3
x=10